Elastic Taboos within the Korean World of Contemporary Art - Gautherot, Franck; Kim Seung-Duk; Matt, Gerald; Yun, Nanjie (Wien : Kunsthalle Wien, 2007)
Bahc Yiso ; Baik Hyunjhin ; Bong Joon-ho ; Bubblyfish (Kim Hae-young) ; Choi Jeong Hwa ; Ginhongsok ; Gontarski, Steven ; Kim Han-yong ; Kim, Sunny ; Lee Kang-So ; Lee Noori ; Lee Sang-hoon ; Lee Seulgi ; Lee U-Fan ; Ou Hein-Khun ; Park Chan-wook ; Park Junebum ; Park Seo-Bo ; Shin Hak-chul ; Yung Yeondoo
Elastic Taboos within the Korean World of Contemporary Art, Kunsthalle Wien, 2007-02-23. 2007-06-10
boek
Keywords: Korea